MEDICINAL PLANTS USED IN THE TREATMENT OF DIABETES MELLITUS WORLDWID (European Journal of Interdisciplinary Research and Development, 2025)
Currently, diabetes mellitus is one of the most widespread and rapidly developing diseases among both young and adult populations. Significant efforts have been made to prevent this disease. The use of medicinal plants in its treatment, the identification of their components, and the development of pharmaceutical products based on them are progressing rapidly. This article emphasizes the importance of early diagnosis and treatment of diabetes through effective use of medicinal preparations. Furthermore, it highlights the significance of cultivating medicinal plants through modern biotechnological methods, producing pharmaceutical products, and implementing preventive measures. The use of biotechnology to develop high-quality medicines with effective mechanisms of action is also considered one of the key factors. Numerous reviews related to ongoing developments in this field are presented.